National Nutrition Communication Campaign in Indonesia: a cross-sectional study of factors associated with exposure - Leiema Hunt; Abigail Norton; Chantel Daines; Evie Friedbaum; Danica Topham; Ryan Moffat; Scott Torres; Mary Linehan; Hafiza Jusril; Cougar Hall; Benjamin Crookston; Josh West (BMC, 2021)
Abstract Background Reducing childhood stunting continues to be a priority in Indonesia. In 2015, the National Nutrition Communication Campaign (NNCC) implemented mass media and interpersonal communication (IPC) interventions to disseminate stunting-related information. Whereas other studies of the NNCC's impact on attitudes and behaviors are currently underway, the purpose of this study was to better understand the factors associated with exposure to the media and IPC components of the NNCC. Methods A cross-sectional survey was conducted following the NNCC media and IPC campaigns in rural Indonesia. The final study sample included 1734 mothers. Survey data was collected from each participant by trained interviewers using an electronic tablet. Responses relating to demographic and socioeconomic factors, use of social media and WhatsApp, and electronic device ownership were analyzed. Logistic regression analyses, using SAS version 9.4, were conducted to evaluate the relationship between technology-related items and exposure to both the media and the IPC interventions. Results Owning an internet device (OR = 1.643, CI = 1.237-2.183, p < 0.001), accessing social media (OR = 1.81, CI = 1.32-2.49, p < 0.001), using a device to access health information (OR = 2.068, CI = 1.469-2.911, p < 0.0001), and accessing WhatsApp (OR = 1.663, CI = 1.175-2.355, p < 0.05) were positively related to exposure to NNCC messages meant to change behavior to decrease stunting. In separate analyses, owning an internet device (OR = 0.609, CI = 0.459-0.81, p < 0.001) accessing social media (OR = 0.626, CI = 0.459-0.854, p < 0.05), using a device to access health information (OR = 0.528, CI = 0.377-0.740, p < 0.001), and accessing WhatsApp (OR = 0.688, CI = 0.489-0.968, p < 0.05) were negatively related to IPC exposure. Mothers with access to internet-accessible devices were more likely to be exposed to the media campaign component to decrease stunting while mothers without access to internet-accessible devices were more likely to be exposed through IPC. Conclusions Mothers who owned devices that could access the internet were more likely to have been exposed to the media campaign component to decrease stunting by behavior change but were less likely to participate in IPC activities. The opposite was true for mothers who did not have access to internet-accessible devices. These findings may be used to inform future community health efforts in rural Indonesia and similar regions that may be considering the use of both mass media and interpersonal interventions to influence health behaviors in order to decrease stunting.